Synthesis, Growth Mechanism and Optical Properties of Colloidal Wurtzite ZTe (Z=Zn, Cd) Nanoplatelets - Wang, Fei (Curtin University, 2019)
This research work investigates the colloidal synthesis, growth mechanism and optical properties of colloidal wurtzite ZTe (Z=Zn, Cd) nanoplatelets. We have successfully synthesized two-dimensional wurtzite ZnTenanoplatelets with a thickness of about 1.5 nm by using polytellurides as tellurium precursor and prepared ribbon-,shield- and bullet-like CdTe nanoplatelets from a step-wise conversion of CdTe magic-sized nanoclusters by simply tailoring the reactivity of tellurium precursor.